2022
DOI: 10.1208/s12249-022-02337-2
|View full text |Cite
|
Sign up to set email alerts
|

Clove Oil Endorsed Transdermal Flux of Dronedarone Hydrochloride Loaded Bilosomal Nanogel: Factorial Design, In vitro Evaluation and Ex vivo Permeation

Abstract: The goal of this study was to develop a bilosomal gel formulation to enhance transdermal permeability of dronedarone hyrdrochloride (DRN) which suffers from poor oral absorption and limited bioavailability. To overcome this obstacle, bilosomes were successfully prepared using 23 full-factorial design. Span®40, cholesterol, sodium deoxycholate (bile salt), clove oil (permeability enhancer), and either Tween® 60 or Tween® 80 (edge activator) were used in bilosome preparation by ethanol injection method. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Another poor orally bioavailable drug, dronedarone hydrochloride (DRN), was also formulated into bilosomal nanogel to enhance transdermal permeability and bioavailability. The optimized bilosomal gel formula demonstrated an in vitro drug release of 57.0 ± 8.68% relative to 13.3 ± 1.2% from drug suspension after 12 h. The ex vivo permeation study findings showed an enhanced skin permeation of 21.23 ± 1.54 µg/cm 2 h across rat skin and collectively showed the superior efficacy of bilosomal gel compared to free drug suspension [ 75 ].…”
Section: Bilosomes As Nanocarrier Drug Delivery System For Treating V...mentioning
confidence: 99%
“…Another poor orally bioavailable drug, dronedarone hydrochloride (DRN), was also formulated into bilosomal nanogel to enhance transdermal permeability and bioavailability. The optimized bilosomal gel formula demonstrated an in vitro drug release of 57.0 ± 8.68% relative to 13.3 ± 1.2% from drug suspension after 12 h. The ex vivo permeation study findings showed an enhanced skin permeation of 21.23 ± 1.54 µg/cm 2 h across rat skin and collectively showed the superior efficacy of bilosomal gel compared to free drug suspension [ 75 ].…”
Section: Bilosomes As Nanocarrier Drug Delivery System For Treating V...mentioning
confidence: 99%
“…Prior to starting the experiment, the frozen skin was thawed till reaching room temperature. This study was implemented utilizing the USP dissolution apparatus II by applying the same conditions utilized in the in vitro drug release study [33,34]. The newly born rat skin was fixed on the glass cylinder having a surface area of 4.908 cm 2 .…”
Section: Ex Vivo Permeation Studymentioning
confidence: 99%
“…In addition, bile salts greatly reduce the temperature at which lipids undergo phase transition, resulting in bilosomal vesicles that are extremely deformable and flexible at physiological temperature. The flexibility of bilosomal vesicles greatly facilitates transdermal application through enhancing penetration into the skin's deep layers [23]. Significantly, the presence of bile salts, sodium deoxycholate (SDC), greatly improves the stability of bilosomal vesicles, in comparison to other traditional vesicles [24].…”
Section: Introductionmentioning
confidence: 99%